Simple Detection Methods for Senescent Cells: Opportunities and Challenges - Faragher, Richard G. A. (Frontiers in Aging, 2021)
Cellular senescence, the irreversible growth arrest of cells from conditional renewal populations combined with a radical shift in their phenotype, is a hallmark of ageing in some mammalian species. In the light of this, interest in the detection of senescent cells in different tissues and different species is increasing. However much of the prior work in this area is heavily slanted towards studies conducted in humans and rodents; and in these species most studies concern primary fibroblasts or cancer cell lines rendered senescent through exposure to a variety of stressors. Complex techniques are now available for the detailed analysis of senescence in these systems. But, rather than focussing on these methods this review instead examines techniques for the simple and reproducible detection of senescent cells. Intended primary for the non-specialist who wishes to quickly detect senescent cells in tissues or species which may lack a significant evidence base on the phenomenon it emphasises the power of the original techniques used to demonstrate the senescence of cells, their interrelationship with other markers and their potential to inform on the senescent state in new species and archival specimens.